The Moderating Effect of Macroprudential Policies on the Relationship Between the Effectiveness of the Board of Directors in Shaping the Bank's Risk-Taking Behavior - Fariska, Putri; Khaerunisa, Alia (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Macroeconomic instability in 2020 caused by COVID-19 can affect the stability of the country's financial system and trigger risks to banking performance. The implementation of macroprudential policies and the effectiveness of the board of directors as policy implementers can be one of the solutions to this problem. The purpose of this study is to see how the influence of macroprudential policies and the effectiveness of the board of directors in shaping bank risk-taking behavior. The method used is panel data regression method and moderation regression with a sample of 43 banks listed on the Indonesia Stock Exchange including banks that consistently published their financial statements for the last five years. The results showed that partially only the effectiveness of the board of directors and company size affected bank risk-taking behavior, while macroprudential policies, macroprudential policies that moderate the effectiveness of the board of directors, and inflation were considered to not affect bank risk-taking behavior, this was due to differences in bank-specific characteristics, the effectiveness of corporate governance, policy implementation in the form of policy easing and tightening, and the interaction between macroprudential policies and monetary policy. However, simultaneously the independent variables and control variables have a significant influence on bank risk-taking behavior.